The evolution of the supervisory reporting framework for the EU banking sector - Paolo Poloni (European Central Bank (ECB), 2024)
Supervisory data are typically not conceived for statistical purposes or considered "official statistics", but they are disclosed to the public, either directly by the supervised institutions or indirectly by the competent authorities. This disclosure is required under Pillar 3 of the Basel framework on banking supervision. The aim of the framework is to promote market discipline, whereby market participants monitor the risks and financial positions of banks and take action to guide, limit and price their risk-taking to safeguard financial stability. The disclosure of supervisory data is therefore a public good. In addition, supervisory data can be a reliable source for official statistics such as financial accounts. On the other hand, the nature of supervisory data differs from that of standard official statistics and its quality is subject to a robust assessment framework, with distinct particularities. The aim of this paper is to analyse the EU supervisory reporting framework from an institutional and policy perspective, in view of its potential and desirable evolution over time, including its possible integration with the statistical framework. The paper is split into three main parts. First, it describes the historical and current EU institutional settings, including the role of the European Banking Authority (EBA) reporting framework and the role of the Single Supervisory Mechanism (SSM), focusing on the data quality assessment framework and the publication of supervisory statistics. Current shortcomings are also analysed. In the next section, the paper describes the possible future evolution of the framework, based mainly on three recent developments: (i) the recommendations of the EBA feasibility study on integrated reporting (common data dictionary, joint governance, central data collection point), (ii) the European Commission's strategy on supervisory data in EU financial services, and (iii) the "better data sharing" legislative initiative, proposed by the European Commission and elaborated on by the European Parliament. Finally, the paper proposes several design choices and policy principles that could inspire such evolution under certain constraints and at low cost. The focus is on the application of the Basel Committee on Banking Supervision (BCBS) 239 principles for supervisory reporting, the interlinkages between supervisory reporting and Pillar 3 disclosure, compliance with BCBS Core Principle 10 (CP 10) on supervisory reporting and the management of ad hoc reporting requirements.
Keywords: C81; G21; G28; G38; 330; supervisory reporting; Pillar 3; data integration; reporting policy; data quality; banking supervision; banking system; data collection; banking policy; official statistics